Comparative prevalence of atopic sensitization in the border areas between Russia and Finland - O. A. Markelova (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Current century has been highlighted with rise in allergic pathology, and environment markedly affects it via epigenetic mechanisms. Allergy research in Russia and Finland has been conducted for many years, of larger scale recorded in the latter, still being maintained over time. Atopy prevalence was studied in the border areas in both countries. The level of total, dietary, inhaled IgE level, as well as dietary and inhalation range were examined. The Phadiatop® radio allergen sorbent test was used (UniCAP 1000 v.2; Pharmacia Upjohn, Uppsala, Sweden), with cut-off point: IgE > 110 kUA/l and sIgE > 2.5 kUa/l and 0.35 kUA/l. The study was subdivided into 2 stages conducted during 2003 and 2010/2012 timeframe. Stage 1 was performed with children from Finland (n = 344), Russia (n = 427), aged 7—15 years, whereas stage 2 — 180 subjects (Finland, n = 98, Russia, n = 82). Results. It was found that total IgE level was higher in children from Finland. The inhaled sIgE in 2003 and 2010/2012 was higher among children from Finland, p = 0.019 and p = 0.027, showing temporal elevation. In 2003, dietary sIgE was higher among those from Finland (27.6% and 18.3%), p = 0.142, whereas in 2010/2012 it was decreased by 2- and 3-fold in subjects from Finland and Russia, respectively. In 2003, high atopy rate against dust mites, cats, timothy, birch, and dogs was found in Russia, which was increased at stage 2. Such parameter was most evidently elevated for timothy — by 2-fold, p = 0.176, wormwood — by 2-fold, p = 0.312, equine allergens — by 2-fold, p = 0.563, canine allergens — by 1.5-fold, mite — by 1.5-fold, p = 0.220. In 2003, atopy rate in Finland to canine allergens reached 26.5%, timothy — 24.5%, birch — 20.4%, feline allergens — 20.4%. In 2010, it was noted rise in atopy rate mainly to dust mites — by 2-fold, equine allergens — by 2-fold. In 2003, atopy rate in Russia to egg, milk, and wheat prevailed, whereas in Finland it was mostly found against milk, nuts, wheat, eggs, in both cases declined in dynamics. Interestingly, no sensitization to fish in subjects from Russia and Finland was observed at both stages. Finally, at the stage 2 dietary atopy rate was declined in both countries. Differences in atopic sensitization as well as during 7—9 year follow-up observation were preserved between both subject cohorts from Finland and Russia.